Pluralisme et Délibération : enjeux en philosophie politique contemporaine (University of Ottawa Press, 1999)
This work with plural voices is resolutely placed in an interdisciplinary perspective. Nine leading authors, working from diverse backgrounds, confront the current crisis of democracy. A central thesis orders the work of analysis: this crisis has its origin in the forgetting of the very notion of democracy, in the rejection of any basic problematic. Identity and difference, community and pluralism, individual and collective rights, public discourse and the legitimation of values, so many crucial problems for the renewal of democracy and its public practice, so many centers around which the reflection of contemporary political philosophy revolves. . This is what each of the contributions questions here. A common thread runs through them: the question of recognizing identity and difference.